Longitudinal Study of Dental Implants in HIV−Positive Patients. Issue 2 (28th September 2021) - Neumeier, Toni Tien; Reddy, Michael; Geurs, Nicolaas; Hill, Jeff; Neumeier, Harold
Abstract: Purpose: This study compared the clinical outcome of dental implants and their implant‐supported restorations over a 3‐year period involving patients both positive and negative for the human immunodeficiency virus. Materials and Methods: Twenty patients testing positive for the human immunodeficiency virus were recruited for this study. Twenty‐one negative control patients were also selected, for a total of forty one patients. Diagnostic impressions were collected and cone beam computed tomography images were obtained. Implant size and positioning were planned using cone beam computed tomography software. Two stage or single surgery was performed as determined by the surgeon (periodontist). After a 6‐month healing period, definitive impressions were fabricated using polyvinyl siloxane impression material. Implant stability quotient values were obtained at the time of surgery and placement of the restoration. Screw‐retained custom titanium abutments were designed, milled, and placed with 25 N·cm torque using a calibrated torque controller. Porcelain fused‐to‐metal complete coverage restorations were then cemented with elastomeric resin implant cement. Implants and restorations were assessed at 6‐month intervals over a period of 3 years for stability, peri‐implant health, and patient satisfaction. Results: Over the 3‐year period, 25 of 42 implants placed in the negative control group were assessed, and 17 of 27 implants placed in the positive control group were evaluated. The overall patient retention rate was 77%. At the 3‐year follow up, restorations examined were fully functional and causing no pain. Overall implant retention within the positive group was 96%. Implant retention within the negative control group was 100%. No differences were noted between groups for bone loss based on statistical tests. Conclusion: Within the limitations of this clinical investigation, the presence of human immunodeficiency virus per se was not a contraindication to dental treatment with implant‐supported restorations.